Vocative and diminutive forms in Robert Louis Stevenson’s fiction: A corpus-based study - Dossena, Marina (International Journal of English Studies, 2012)
This paper takes a corpus-based approach to the study of vocative and diminutive forms in the prose fiction and drama of the Scottish author Robert Louis Stevenson. In such texts, the coexistence, and indeed the coalescence, of Scots and (Scottish Standard) English is one of the most important traits in their author’s distinctive style. The aim is to assess whether the use of diminutive forms together with vocative ones may constitute a syntactic unit in which semantic and pragmatic values are mutually reinforced. In addition to a specially-compiled corpus of Stevenson’s texts, the investigation will consider occurrences of the same structure in the imaginative prose section of the Corpus of Modern Scottish Writing, which will be used as a control corpus.